Système Solaire Hybride Électrique/Thermique à base de Nano Fluide - Ines AYARI (My University, 2023)
Our work contributes to improving the performance of hybrid photovoltaic-thermal (PVT) systems in terms of electrical and thermal efficiency by reducing the temperature of the photovoltaic panel to increaseitsenergyefficiency. A numerical simulation based on multiple modeling and optimization methods has been developed to study the effect of various parameters, such as solar radiation, nanofluidvelocity, and convective heattransfer coefficient. The obtainedresults show that the optimal parameters to maximize electrical and thermal yields are as follows: For electrical efficiency, we have solar radiation of 600W/m², nanofluidvelocity of 0.05 m/s, and convective heattransfer coefficient of 30 m²K/W. On the other hand, for thermal efficiency, the values are 1000 W/m², 0.05 m/s, and 6.5 m²K/W, respectively. Additionally, the coolantfluidused in the cooling system is Al2O3. The combination of these optimal factorsallowed us to achieve thermal and electricalyields of 83.5% and 14.23%, respectively. The proposed simulation model offers a reliableapproach to study and improve the performance of PVT systems whileminimizing computation time ------------------------------------------------------------------------------------ عملنا يساهم في تحسين أداء أنظمة الطاقة الكهروضوئية الحرارية المتكاملة من حيث الكفاءة الكهربائية والحرارية عن طريق خفض درجة حرارة لوحة الطاقة الكهروضوئية لزيادة كفاءة الطاقة. تم تطوير نموذج محاكاة عدديا ستنادًا إلى أساليب التصميم والتحسين المتعددة لدراسة تأثير مجموعة متنوعة من المعاملا تمثل إشعاع الشمس وسرعة سائلا لنانو ومعامل نقل الحرارة الحملي. أظهرت النتائج المتحصلة أن المعاملات الأمثل لتحقيق أقصى كفاءات كهربائية وحرارية هي كالتالي: بالنسبة للكفاءة الكهربائية، لدينا إشعاع شمسي بقدرة 600 واط/م ² ،سرعة سائلا لنانو 0.05 م/ث،ومعامل نقل الحرارة الحملي 30 م ²ك/و. بالمقابل، بالنسبة للكفاءة الحرارية، تكون القيم 1000 واط/م ² ، 0.05 م/ث،و 6.5 م ²ك/و، على التوالي. بالإضافة إلىذلك، يتم استخدام سائلا لتبريدأوكسيد الألومنيوم في نظام التبريد. جمع هذه العوامل الأمثل سمح لنا بتحقيق كفاءات حرارية وكهربائية بنسب 83.5 % و 14.23 % على التوالي. يقدم النموذج المحاكاة المقترح نهجًا موثوقً الدراسة وتحسين أداء أنظمة الطاقة الكهروضوئية الحرارية المتكاملة مع تقليل وقت الحساب . ----------------------------------------------------------------------------------- Notre travail contribue à l'amélioration des performances des systèmes photovoltaïques thermiques hybrides (PVT) en termes d'efficacité électrique et thermique, en réduisant la température du panneau photovoltaïque pour augmenter son efficacité énergétique. Une simulation numérique basé sur plusieurs méthodes modélisation et d'optimisations a été développé pour étudier l'effet de différents paramètres, tels que les radiations solaires, la vitesse du nano fluide et le coefficient d’échange convective. Les résultats obtenus montrent que les paramètres optimaux pour maximiser les rendements électriques et thermiques sont : Pour l’efficacité électrique on a les radiations solaires 600W/m², la vitesse du nano fluide de 0.05 m/s et un coefficient d’échange convectif30 m²K/ W, par contre pour l’efficacité thermique les valeurs sont : 1000 W/m², 0.01 m/s, 6.5 m²K/ W. De plus, le fluide caloporteur utilisé dans le système de refroidissement est l'Al2O3. La combinaison des facteurs ayant de valeurs optimales nous ont permis d'atteindre des rendements thermiques et électriques 83.5 %, 14.23 % respectivement. Le modèle de simulation proposé offre une approche fiable pour étudier et améliorer les performances des systèmes PVT, tout en minimisant le temps de calcul.